The Effect of Job Satisfaction and Organizational Culture on Employee Performance of the Royal Hotel in East Aceh District - Syardiansah Syardiansah; Abdul Latief; Muhammad Nur Daud; Windi Windi; Agung Suharyanto (Budapest International Research and Critics University, 2020)
This study aims to determine the effect of job satisfaction and organizational culture on the performance of employees of The Royal Hotel in East Aceh Regency. The sample used in this study amounted to 42 respondents. The sampling technique used in this study uses a non probability sampling technique that is saturated sampling. The data analysis method uses multiple linear regression analysis, t test, F test, and coefficient of determination analysis. The regression equation produced in this study Y = 2.984 + 0.460X1 + 0.203X2. Job satisfaction has a positive and significant effect on employee performance at The Royal Hotel in East Aceh Regency. This is evidenced from the t test in which the t value of 0.029 <0.05 was obtained. Organizational culture has a positive and significant effect on employee performance at The Royal Hotel in East Aceh Regency. This is evidenced from the t test in which the t-value of 0.035 <0.05 was obtained. Job satisfaction and organizational culture simultaneously have a significant effect on the performance of employees of The Royal Hotel in East Aceh Regency. This is evidenced from the F test where F sig 0.034 <0.05. From the results of the analysis of the coefficient of determination can be explained that job satisfaction and organizational culture affect the performance of employees of The Royal Hotel in East Aceh Regency by 58.6%. While the remaining 41.4% is influenced by other variables not examined in this study.